KEGAGALAN AKUNTANSI DALAM MENANGGULANGI FRAUD: (PERSPEKTIF POSTMODERN) - Anantawikrama Tungga Atmadja; Komang Adi Kurniawan Saputra (Jurnal Aplikasi Akuntansi, 2018)
Fraud often cannot be eliminated in the operational activities of the organization, including in the public sector organizations. In a sense, the accounting system applied cannot prevent fraud as idealized. This condition shows that accounting as a narrative cannot be separated from the application of other narratives adopted by humans as accounting agents. This paper will discuss how accounting, including internal control within it, is understood as a narrative in the frame of postmodernism. As a narrative, accounting must compete with other narratives to become a habitus and give a disposition to act on the agent who adheres to it. Humans, as accountants, must also be positioned as complex creatures and not only moved on the basis of mere rationality. This understanding is expected to provide a more holistic understanding of the background of the failure and success of accounting in overcoming fraud and suggestions for corrective actions.